2021
DOI: 10.3389/fpubh.2021.679853
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends and Hotspots of Other Infectious Diarrhea (OID) in Mainland China: A Population-Based Surveillance Study From 2004 to 2017

Abstract: Background: The incidence of other infectious diarrhea (OID) ranked second in class C notifiable disease in China. It has posed a great threat to public health of all age groups. The aim of this study was to investigate the epidemiological trends and hotspots of OID in mainland China.Materials and Methods: Incidence and mortality data for OID stratified by date, age and region from 2004 to 2017 was extracted from the data-center of China public health science. Joinpoint regression and space-time analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…In addition, consistent with previous studies, the incidence rate of children is significantly higher than that of adults, and the incidence rate is the highest in the 0 to 4 years old group. [ 21 ] T The reasons for this result may be related to the immature immune system of children, the imperfect development of the gastrointestinal function, and the failure to establish good hygiene habits. [ 22 , 23 ] Therefore, it is necessary to strengthen the publicity and education of food safety knowledge and improve health awareness for families of children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, consistent with previous studies, the incidence rate of children is significantly higher than that of adults, and the incidence rate is the highest in the 0 to 4 years old group. [ 21 ] T The reasons for this result may be related to the immature immune system of children, the imperfect development of the gastrointestinal function, and the failure to establish good hygiene habits. [ 22 , 23 ] Therefore, it is necessary to strengthen the publicity and education of food safety knowledge and improve health awareness for families of children.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, an investigation by Wang et al reported that NPIs significantly suppressed the spread of acute diarrhea caused by common enteroviruses throughout China, but this effect was not as strong for acute diarrhea caused by intestinal bacteria ( 39 ). This might be because people—especially children—who have bacterial diarrhea are more likely to experience fever and severe symptoms and are also more likely to seek medical care, even during the COVID-19 pandemic ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in this country, a group of infectious diseases with diarrhea as the main symptom other than cholera, dysentery, typhoid and paratyphoid, is defined as other infectious diarrhea (OID), which ranks second in class C notifiable diseases and works as an efficient index reflecting the diarrheal burden (Zheng et al 2023, Chinese Center For Disease Control And Prevention 2022. There is a constantly increasing trend of OID in China and projected to trigger considerable burdens in the future (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 99%